Representations of music in nineteenth-century French art - Pittion, Una (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2021)
In the abundant production shown in Salons - official and non-official - during the Second Empire and the Third Republic until 1900, a number of paintings have music as their theme. They form occasional clusters, corresponding to current fashionable musical tastes and artistic styles. This production testifies to the emergence of new musical forms and to the increased availability of music in French society of the times. Attendance at opera and symphonic concerts spread and practising an instrument for pleasure particularly the piano became a regular form of leisure in bourgeois households. In this production, allegories of Music, inspired by the Baudelaire s idea of the correspondence between all the arts and centred around the emblematic figure of Orpheus, were destined for the decoration of public buildings, while most representations of musical performances were composed in the traditional format of interior genre painting, expected by private buyers. On the other hand, this dissertation seeks to show that the production of some painters does not just echo in a general way, their musical preferences notably for Wagnerian opera, but that in a few of their works, they seek to express in visual terms, the special aesthetic emotion created by the shared musical moment they depict. Going beyond the narrative or the symbolical, some painters made use of a greatly enriched colour palette, to create harmonies, assonances and dissonances, or occasionally had recourse to line to create a sense of musical rhythm. These few works by Gustave Courbet, Édouard Manet, Edgar Degas, Henri Fantin-Latour, Auguste Renoir, George Seurat et Henri Lerolle are exceptional attempts to translate in visual terms, within the space of a fixed image, the unique aesthetic emotion created by music, an emotion that only takes place in time.
APPROVED
Keywords: Music, Art, French, Nineteenth Century, France, Representations